Come Closer: Experimental Investigation of Robots' Appearance on Proximity, Affect and Trust in a Domestic Environment. (December 2020) - Miller, Linda; Kraus, Johannes; Babel, Franziska; Messner, Matthias; Baumann, Martin
From once being utopian, robots become more and more common in public and private social life. One area of application are robots, which are able to perform chores in domestic environments. To support users accustoming to the new robot companion, psychological mechanisms that enhance the interaction with robots need to be understood. In this research, the effects of robot's height and manipulator position on proximity, affect and trust with regards to a humanoid robot were investigated in a laboratory experiment. Results indicated an effect of robot's height on the comfort distance. On the other hand, a habituation effect after a second robot-human approach was found, in which the influence of the robot's height on proximity diminished. Similar effects with an anxiety decrease and trending trust increase in the tall robot over time emphasize the importance of first encounters, which should be paid special attention to by designers of robotic systems.